Analisis Ratio Decidendi Penjatuhan Pidana Mati Terhadap Pelaku Tindak Pidana Narkotika Yang Rumusan Pasalnya Tidak Ada Ancaman Pidana Mati (Studi Putusan No. 241/Pid.Sus/2019/Pn.Tjb) - Antonius Bangun Silitonga; Alvi Syahrin; Mahmud Mulyadi; M. Eka Putra (Iuris Studia: Jurnal Kajian Hukum, 2021)
In the preamble to letter c of Law Number 35 of 2009 concerning Narcotics, it is stated that narcotics on the one hand are drugs or substances that are useful in the field of medicine or health services and development of science and on the other hand can also cause dependency which is very detrimental if misused or used without control. And close and careful supervision. In Law No.35 of 2009 on Narcotics, there are several articles that use the death penalty, including: Article 113 paragraph (2), Article 114 paragraph (2), Article 116 paragraph (2), Article 118 paragraph (2), Article 119 paragraph (2), Article 121 paragraph (2), Article 133 paragraph (2) of Law No.35 of 2009 on Narcotics, states that perpetrators of criminal acts can be sentenced to death or imprisonment. This research includes normative legal research. Data analysis data processing basically depends on the type of data, for normative legal research that only recognizes secondary data, which consists of primary, secondary and tertiary legal materials. The secondary data includes research on positive legal inventories, legal principles, clinical legal research, systematics of statutory regulations, court decisions, legal history and comparative law. The defendant charged with the Primair indictment is Article 114 paragraph (2) in conjunction with Article 132 paragraph (1) of Law No. 35 of 2009, while the Subsidiary indictment is Article 112 paragraph (2) in conjunction with Article 132 paragraph (1) of Law No. 35 of 2009 concerning Narcotics, however the Judge’s Verdict is a subsidies charge with the death penalty, whereas the Article in the Subsidair Indictment has a maximum sentence of 20 (twenty) years in prison. The Panel of Judges can be deemed incompetent in carrying out their duties, because they ignore the value of legal certainty in their decisions, so that what arises is injustice for both the perpetrator and the community, besides that in accordance with the provisions of Article 197 paragraph (2) of the Criminal Procedure Code, the decision is declared null and void because it is not in accordance with the content of Article 197 paragraph (1) letter c of the Criminal Procedure Code and the Decision of the Supreme Court of the Republic of Indonesia number: 321 K / Pid / 1983 dated 26 May 1984 and the Decision of the Supreme Court of the Republic of Indonesia Number 694 K / Pid / 1984 dated 15 May 1994 resulted in the decision null and void.